Metal sulfide-based process analysis for hydrogen generation from hydrogen sulfide conversion. (13th August 2019) - Reddy, Sharath; Nadgouda, Sourabh G.; Tong, Andrew; Fan, L.-S.
Abstract: Fossil fuel power plants often generate sulfur species such as hydrogen sulfide or sulfur dioxide due to the sulfur content of the raw feedstocks. To combat the associated environmental, processing, and corrosion issues, facilities commonly utilize a Claus process to convert hydrogen sulfide (H2 S) to elemental sulfur. Unfortunately, the potential for H2 production from H2 S is lost in the Claus process. In this study, two chemical looping process configurations utilizing metal sulfides as chemical intermediates for sulfur recovery are investigated: (1) sulfur recovery (SR) system for sulfur production; (2) sulfur and hydrogen (H2 ) recovery (SHR) system for sulfur and H2 and production utilizing staged H2 separation. Since, H2 yield and sulfur recovery in a single thermal decomposition reactor is limited by low H2 S equilibrium conversion, a staged H2 separation approach is used to increase H2 S conversion to H2 using the SHR system. Steady-state simulations and optimization of process conditions are conducted in Aspen Plus (v10) simulation software for the chemical looping process configurations and the Claus process. An energy and exergy analysis are done for the Claus and chemical looping processes to demonstrate the relative contribution to exergy destruction from different unit operations as well as overall exergy and energy efficiency. The two chemical looping process configurations are compared against the conventional Claus process for similar sulfur recovery in a 629 MWe integrated gasification combined cycle power plant. The SHR system is found to be the most efficient option due to a 97.11% exergy efficiency with 99.31% H2 recovery. The overall energy and exergy efficiencies of this chemical looping system are 14.74% and 21.54% points higher than the Claus process, respectively, suggesting more efficient use of total input energy. Highlights: SR and SHR chemical looping systems proposed as alternatives to Claus process. Metal sulfide intermediate used in chemical looping system for H2 S conversion. Sulfur recovery and H2 production demonstrated in SHR system. SHR system has 14.74% points higher energy efficiency than Claus process. SHR system has 21.54% points higher exergy efficiency than Claus process.